UJI KUALITAS SINTESIS KARBON AKTIF DARI PELEPAH AREN TERAKTIVASI ASAM FOSFAT - Neneng Purnamawati (Journal of Research and Education Chemistry, 2023)
Palm fronds which contain a lot of cellulose have the potential to be used as active carbon. There are three stages in making activated carbon from sugar palm fronds, namely the dehydration process, carbonization process, and activation process using phosphoric acid activator (H3PO4) with a concentration of 1M at temperatures of 450°C and 600°C. The aim of this research is to determine the effect of carbonization temperature on the quality of activated carbon from sugar palm fronds. The activated carbon quality tests carried out include yield tests, water content tests, ash content tests and iodine absorption tests. The results of testing the quality of activated carbon showed that optimal conditions were at a temperature of 450°C with a yield of 22.189%, a water content of 2.562%, a total ash content of 5.86% and an iodine absorption capacity of 81.423 mg/g.